2014
DOI: 10.4269/ajtmh.12-0598
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to Promote Patients' Adherence to Antimalarial Medication: A Systematic Review

Abstract: Abstract. Non-adherence as a major contributor to poor treatment outcomes. This study aimed to explore the effectiveness of existing interventions promoting adherence to antimalarial drugs by systematic review. The following databases were used to identify potential articles: MEDLINE, EMBASE, the Cochrane CENTRAL, and CINAHL (through March 2013). From 1,813 potential papers identified, 16 studies met the selection criteria comprising 9,247 patients. Interventions were classified as packaging aids, visual media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“… reported that the absence of a difference in adherence between the intervention and control groups was probably because the population under study consisted of soldiers who stayed together after returning from a malaria‐endemic area. Adherence to malaria prophylaxis has been reported to be inadequate, mainly because of adverse events and forgetfulness . As stated above, multifaceted interventions featuring interactive education and training help to promote adherence in a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%
“… reported that the absence of a difference in adherence between the intervention and control groups was probably because the population under study consisted of soldiers who stayed together after returning from a malaria‐endemic area. Adherence to malaria prophylaxis has been reported to be inadequate, mainly because of adverse events and forgetfulness . As stated above, multifaceted interventions featuring interactive education and training help to promote adherence in a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions that have been shown to improve patient adherence to antimalarial drugs include packaging and community education. 46 ACTs are now mostly available in factory packaged unit dose packs blister packs with illustrated instructions, therefore additional room for improvement may be limited. One possible modification could be improved instructions in local languages.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Malawi used MEMS containers and found 100% adherence to artemether-lumefantrine (AL) by self-report and lower adherence (92%) by MEMS [ 8 ]. However, ACTs are now typically dispensed in blister packs designed to improve adherence [ 15 ] and look considerably different than MEMS containers. This may result in over-estimated adherence, as patients using MEMS are likely to be aware that their adherence is being monitored and their experience is no longer comparable to that of patients receiving unit doses in their customary packaging.…”
Section: Introductionmentioning
confidence: 99%